Kontribusi Asosiasi Peternakan Ayam Broiler Pada Anggotanya - Roisu Eny Mudawaroch; Sunardi Sunardi (Universitas Muhammadiyah Purworejo, 2020)
The existence of the community allows an increase in the business of laying hens. The existence of the “Berkah telur Makmur’ association motivates these breeders to emerge because the breeders feel that the laying hen business can support their social relationships and can be developed as a family business. The purpose of this study was to determine the benefits of joining a laying hen association in the Purworejo area. This research was conducted at the association of laying hens in